Diplomado en Medición de hidrocarburos, Módulo II: Sistemas de medición de aceite - Valencia Figueroa, Javier (My University, 2001)
For best results, the prover temperature and the meter temperature should be stabilized. When a prover has been off line, more time is required for temperature equilibrium to be attained. The ability to detected temperature changes during proving is essential if accurate results are to be obtained with a meter prover.
Keywords: publications; corcering; provers; interpolation; measures